Bimodal Polymer Brush Tethered to a Solid / Liquid Interface Brosse polymère bimodale ancrée à interface solide / liquide - Dan-Brandon N.; Argillier J. F.; Tirrell M. (Oil & Gas Science and Technology, 2006)
The structure of a dense polymer brush with bimodal molecular weight distribution in good solvent is described. The bimodal brush can be divided into two layers. The layer that is adjacent to the surface contains segments from both constituent chains. The second layer contains only the 'dangling' ends of the higher molecular weight chains. The free energy of the brush is calculated using a Flory type approach. We find that at equilibrium the higher molecular weight chains are stretched in the layer near the surface compared to the shorter chains. This stretching decreases the concentration, thereby reducing segment-segment interaction energy, at the cost of a stretching penalty for the higher molecular weight chains. The degree of stretching is a function of the ratio of surface densities only. Cet article décrit la structure d'une brosse polymère dense à répartition bimodale des poids moléculaires dans un bon solvant. La brosse bimodale peut être divisée en deux couches. La couche adjacente à la surface contient des segments des deux chaînes constitutives. La seconde couche ne contient que les extrémités libres des chaînes à fort poids moléculaire. L'énergie libre de la brosse est calculée selon une formule de type Flory. Nous avons constaté qu'en position d'équilibre, ce sont les chaînes de plus fort poids moléculaire qui sont étirées dans la couche proche de la surface, et non les chaînes plus courtes. Cet étirement réduit la concentration, d'où une réduction de l'énergie d'interaction segment-segment, avec pour conséquence une pénalité d'étirement pour les chaînes de fort poids moléculaire. Le degré d'étirement est uniquement fonction du rapport des densités superficielles.